Comparative geometry on plane and sphere: didactical impressions - Makara, Ágnes; Lénárt, István (Teaching Mathematics and Computer Science, 2004)
Description of experiences in teaching comparative geometry for prospective teachers of primary schools. We focus on examples that refer to changes in our students' thinking, in their mathematical knowledge and their learning and teaching attitudes. At the beginning, we expected from our students familiarity with the basics of the geographic coordinate system, such as North and South Poles, Equator, latitudes and longitudes. Spherical trigonometry was not dealt with in the whole project.